Senator John Brooks Henderson, U.S. Senator from Missouri - Mattingly, Arthur Herman (Kansas State University, 1971)
The career of John Brooks Henderson has been overlooked by Missouri historians. This work attempts to partially solve the oversight by focusing on his political career from 1848 until defeat for re-election to the United States Senate in 1869. Out of necessity, many of Henderson's senatorial activities have been deferred to permit examination of his role in the major issues in the decade of the sixties. From candidate for county clerk to United States Senator, Henderson's elective career mirrors the turmoil faced by a politician in the state and nation on the eve of the Civil War. His political ascendancy in the state Democratic party parallels the splintering of party allegiances on the issues of: popular sovereignty, banks, slavery expansion, and the Mexican War. Henderson's attempts to win national office preceding the Civil War were thwarted each time by division within the Democratic party over national questions. When the problem of Missouri's relation to the national government came before the people on the eve of the war, Henderson steadfastly stood for the Union. In the state conventions of 1861 he was an ardent spokesman for the "Unconditional Union" faction. From his first political office to his last, he exemplified character which would not allow him to place party before personal integrity or the country. His devotion to the law and Constitution are clearly evident throughout his career, but was best manifested in his search for a constitutional solution to slavery. Henderson took a leading role in Missouri and the border states, first as the spokesman for President Abraham Lincoln's compensated emancipation and later as the author of the Thirteenth Amendment to the Constitution. After the war, as Chairman of the Senate Committee on Indian Affairs, he sought an equitable answer to the constant friction between Indians and whites by sponsoring the bill that authorized the Indian Peace Commission of 1867. While a commission member, he urged the Indians to accept a new reservation system with a program of government help. He proposed, as Commission spokesman at the meetings, a gradual transition to agricultural pursuits instead of the hunt, because the buffalo were rapidly disappearing. Although successful in obtaining Indian approval, Henderson was unable in the crucial months after the treaties to give his full attention to enacting the necessary congressional legislation to implement the treaty provisions, and successfully settle the difficult problem. His concern in the spring of 1868 was increasingly drawn to the struggle between the President and Congress. Originally a struggle over reconstruction of the southern states, it soon widened into a struggle for control of the national government, culminating in the impeachment of Andrew Johnson. Henderson's vote in the trial is the nearest he came to national fame, when along with six other Republican senators he acquitted the President. For this act of personal integrity and honor he and the others were abused. But unlike the others, Henderson suffered the least permanent harm. In later years he enjoyed influence in the state and national Republican parties and received several nominations for state and national offices.